Modeling and synchronized control of dual parallel brushless direct current motors with single inverter. (August 2018) - Ebadpour, Mohsen; Sharifian, Mohammad Bagher Bannae; Babaei, Ebrahim
Abstract: Parallel connected electrical machines drive systems have received significant attention due to their use in special purpose applications. Recently, control of such systems using a single inverter has been considered for improving stability during uneven load conditions on machines. In this paper, a synchronized control strategy for stable operation of dual parallel brushless direct current motors using a single three-phase inverter is proposed. Control of parallel connected brushless direct current motors suffers from instability under different load torques. To obtain the stability, an effective control method based on master-slave strategy is presented. To analysis the stability, the detail model of the proposed system is developed for an electric vehicle propulsion system. Therein, the motor with the highest load or with lagging rotor position is selected as the master and is directly controlled. The effectiveness of the proposed system is demonstrated by a series of case studies in different operation conditions.